Misremembrance of Options Past: Source Monitoring and Choice - Mather, Mara; Shafir, Eldar; Johnson, Marcia K. (Psychological Science, 2000)
This study reveals that when remembering past decisions, people engage in choice-supportive memory distortion. When asked to make memory attributions of options' features, participants made source-monitoring errors that supported their decisions. They tended to attribute, both correctly and incorrectly, more positive features to the option they had selected than to its competitor. In addition, they sometimes attributed, both correctly and incorrectly, more negative features to the nonselected option. This pattern of distortion may be beneficial to people's general well-being, reducing regret for options not taken. At the same time, it is problematic for memory accuracy, for accountability, and for learning from past experience.